Aplicando estratégias simultâneas de momento e valor no mercado brasileiro - Cruz, Jerckns Affonso (2009)
The theory of Behavioral Finance emerges as a new approach to the financial market, arguing that some events are better explained if the restrictions of investor’s rationality are relaxed. Concepts of psychology and limits to arbitrage are used to model market inefficiencies, bringing up the idea that market can be systematically beaten. This paper proposes a new model, of simple implementation, to explore the abnormal returns from the momentum and mean reversion strategies simultaneously. The idea of a long term momentum effect stronger than the short term effect is introduced, but the empirical results show that the Brazilian market dynamics reject this concept. The model fails to achieve riskless positive returns.